COSENTINO, Daniel do V.; GAMBI, Thiago F. R. História do pensamento econômico: pensamento econômico brasileiro. Niterói: Eduff; São Paulo: Hucitec, 2019 - Cantarino, Nelson Mendes (História Econômica & História de Empresas, 2020)
-